Adaptation and integration of the thinking healthy programme into pregnancy schools in Istanbul, Turkey - Perran Boran; Melike Dönmez; Najia Atif; Anum Nisar; Ezgi Barış; Mahmut Caner Us; Zeynep Meva Altaş; Seyhan Hıdıroğlu; Dilşad Save; Atif Rahman (BMC, 2023)
Abstract Background Perinatal mental health is a major public health concern. In Turkey, public hospitals operate pregnancy schools which provides an opportunity to integrate an evidence-based Thinking Healthy Programme (THP) for perinatal depression. The aim of this study is to adapt the THP for universal use in the group setting and to understand its acceptability and feasibility for integration into the existing antenatal care programme for both face-to-face and online delivery. Methods Following an expert-led adaptation process using the Bernal Framework, field testing was conducted on a group of women and facilitators followed by in-depth interviews (n:8) and group discussions (n = 13). Data were analysed using Thematic Framework Analysis. Results Minor but significant adaptations were made to the individually delivered THP for use in the universal group pregnancy schools. Initial findings indicate that the THP-group version was acceptable to its target population and could be integrated into the antenatal care plan for delivery during face-to-face and online group classes. Conclusion THP is transferable to the Turkish cultural and healthcare context. The THP-group version has the potential to add value to Turkey's existing perinatal healthcare programme.